'Catch me if you can': the myth and reality of criminals' use of juju to evade arrest from the Nigeria police. (15th January 2021) - Aborisade, Richard A.; Adedayo, Sunday S.
ABSTRACT: This research investigates the deployment of juju rituals by criminals to perpetrate crime, ensure invincibility, avoid injury or death, subdue victims, and evade police apprehension. Existing studies have predominantly focused on the use of juju in relation to human and sex trafficking; however, this current study takes a more generalized approach to examine usage across Nigerian-organized crime. It explores perceived potency and exploits of juju-using criminals, police personnel's encounters and experiences in effecting their arrest, and accounts of juju priests on the conducts of juju rituals and spiritual fortifications for their clientele. Qualitative research techniques involving ex-convicts of violent crimes, police personnel and juju priests were adopted. The findings confirm a high level of beliefs in the power and potency of juju rituals, in spite of affiliations to orthodox religions. Police personnel admitted the efficacy of juju rituals which enables criminals with charms to have a supernatural edge over them during arrest operations. Consequently, this study advocates for the recognition of juju practice by the justice system, in order to regulate witchdoctors' activities and provide the necessary support for police personnel.